Goals of care conversations and telemedicine. Issue 7 (September 2021) - Saldivar, Reggie Tiong; Tew, William P.; Shahrokni, Armin; Nelson, Judith
Abstract: Rapid expansion of telemedicine is one of the transformative healthcare consequences of the COVID pandemic. As a result, telemedicine has allowed clinicians to address the needs of older adults with cancer, who faced the highest risks from COVID, while maintaining safety at home. In light of the COVID experience, which is an important source of learning, this article provides guidance on approaches to enhance telemedicine-enabled supportive care for the geriatric cancer patient.